2014
DOI: 10.1111/ijag.12094
|View full text |Cite
|
Sign up to set email alerts
|

Equibiaxial Flexure Strength of Glass: Influence of Glass Plate Size and Equibiaxial Ring Ratio

Abstract: Glass plays an important role in many engineering applications including transparent armor. Determining the actual strength of a glass is problematic because typical glass strength numbers are presented in the literature as ranges. Minor changes in surface finish, composition, test method employed, and processing all influence the mechanical strength of glass. A standardized method needs to be utilized to ensure that strength data can be compared universally. The use of a standard methodology is vital when com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
(26 reference statements)
2
5
0
Order By: Relevance
“…Knoop hardness for the two glasses was equivalent, so this characteristic does not appear to contribute to differences in triaxial or ballistic loading responses for these two glasses. Differences in flexure strength were observed, and these differences have been observed by the authors in a separate study and more recently by Swab et al . But the flexure strength of glass is limited by the surface flaw population size, and those flaws are not necessarily always the same for a given glass at all times in its history.…”
Section: Comparisons Of Measured Properties and Characteristicsmentioning
confidence: 53%
See 1 more Smart Citation
“…Knoop hardness for the two glasses was equivalent, so this characteristic does not appear to contribute to differences in triaxial or ballistic loading responses for these two glasses. Differences in flexure strength were observed, and these differences have been observed by the authors in a separate study and more recently by Swab et al . But the flexure strength of glass is limited by the surface flaw population size, and those flaws are not necessarily always the same for a given glass at all times in its history.…”
Section: Comparisons Of Measured Properties and Characteristicsmentioning
confidence: 53%
“…10,11 Knoop hardness for the two glasses was equivalent, so this characteristic does not appear to contribute to differences in triaxial or ballistic loading responses for these two glasses. Differences in flexure strength were observed, and these differences have been observed by the authors in a separate study 12 and more recently by Swab et al 13 But the flexure strength of glass is limited by the surface flaw population size, and those flaws are not necessarily always the same for a given glass at all times in its history. Similar to the discussion concerning differences of flaw populations on the tin and air sides, flexure strength may play a role during the onset of fracture initiation; however, once massive fragmentation or damage accumulates, those identified differences in flexure strength likely no longer have a contributing role.…”
Section: Comparisons Of Measured Properties and Characteristicsmentioning
confidence: 61%
“…Vitman and Pugh 1 and Ritter et al 2 recommend large overhangs; in the latter paper as much as 1.75. Swab et al 11 showed how an overhang ratio approaching 2 significantly reduced the number of specimens that exhibited edge‐initiated (invalid) fracture. As will be shown later, the large overhang has an unexpected consequence.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the values of strengths measured by a double ring test are somewhat larger at the atmosphere side than at the tin bath side. The values given in the literature for the atmosphere sides are in the range from 180 to 243 MPa, while they are 114 to 147 MPa for the tin bath side . It should be noted that also the ratio of the load to the support ring diameter affects the measured strength values.…”
Section: Resultsmentioning
confidence: 95%
“…By contrast, the strength measured after ion exchange in a salt bath is much higher than the strength reported in this study. For a temperature of 405°C and an ion exchange time of 20 h, the strength of 838 MPa can be interpolated from the data given in Refs . This is an increase in strength by 370%.…”
Section: Resultsmentioning
confidence: 99%